AB0841 Perfectionism in Chronic Pain: Are There Differences between fibromyalgia, Rheumatoid Arthritis and Healthy Controls?. (15th July 2016) - Pinto, A.M.; Pereira, A.T.; Costa, C.; Marques, M.; da Silva, J.A.P.; Macedo, A.
Abstract : Background: Perfectionism has been associated with a plethora of medical conditions and psychopathological symptoms/disorders. 1 However, the potential impact of perfectionism in different chronic pain conditions is scarcely explored. Objectives: Compare patients with fibromyalgia (FM), rheumatoid arthritis (RA) and pain-free controls regarding mean scores of perfectionism dimensions and cognitions; and test if perfectionism dimensions are significantly associated with the disease group. Methods: Participants were recruited among consecutive attendees with FM, RA and pain-free controls at rheumatology and gynecology practices in Coimbra. Patients with FM and RA satisfied currently accepted classification criteria. 2, 3 The absence of chronic pain in healthy controls (HC) was established by a score of zero in the London Fibromyalgia Epidemiological Study Screening 4 . All participants completed the Portuguese versions of the Frost and of the Hewitt and Flett Multidimensional Perfectionism Scales (MPS) and the Multidimensional Perfectionism Cognitions Inventory. To achieve our aims, descriptive analyses, one-way independent ANOVA (followed by post hoc tests) and linear multiple regression (LMR) were performed. Results: The total sample comprised 302 participants [103 FM (34.11%), 98 RA (32.45%) and 101 HC (33.44%)]. Differences between samples were found regarding age (F=30.598; p <.001) and education years (F=25.883; p <.001). Results revealed significant differences between the samples regarding: parental criticism (PC), organization (O), Frost-MPS total score, perfectionism cognitions related with concern over mistakes (CoM) and pursuit of perfection (PP). Post hoc comparisons indicated that FM patients exhibited higher levels than RA patients and HC in all of these variables (except for PP that did not significantly differ between FM and HC). No significant differences were found between RA and HC, except for PC and O, with RA patients scoring higher. Regarding LMR, the model was significant (F(8, 245)=5, 203; p<.001), with PC (β=-.372; t=-5.014; p <.001) and O (β=-.161; t =-2.567; p=.011) significantly predicting the type of sample. Conclusions: FM patients seem to be noticeably more perfectionistic than RA patients and HC, which in turn, do not differ significantly, in the majority of the perfectionism traits and cognitions. PC and O appear to be the most discriminative perfectionism dimensions. Perfectionism seems a variable of utmost importance, especially in FM, and may deserve consideration as a target for interventions. References: Sirois F & Molnar DS (Eds). Perfectionism, health and well-Being. Springer International Publishing, 2016. Wolfe F et al. The American College of Rheumatology. Criteria for the classification of Fibromyalgia. Report of the multicenter criteria committee. Arthritis Rheum 1990; 33: 160–172. Arnett FC et al. The American Rheumatism Association 1987 revised criteria for the classification of rheumatoid arthritis. Arthritis Rheum, 1988; 315–324. White KP et al. Testing an instrument to screen for fibromyalgia syndrome in general population studies: The London Fibromyalgia Epidemiology Study Screening Questionnaire. J Rheumatol. 1999; 26: 880–884. Disclosure of Interest: None declared